Spray deposition promoted by different sprayers on the mountain coffee crop (Coffee Science - ISSN 1984-3909, 2016)
Coffee crop is an important agricultural activity in Brazil, but with major technological challenges in disease and pest control. This study aimed to evaluate the spray deposition promoted by different sprayers on the mountain coffee crop. The trial was carried out in a randomized blocks design, with 11 treatments and 4 replicates. Different equipments were used in the pesticide applications: motorized knapsack sprayer, adapted sprayer tricycle, adapted motorized knapsack sprayer and manual knapsack sprayer, combined with electrostatic technology and silicone adjuvant in different application rates. Initially, a study was conducted to characterize the droplet spectrum with the use of water sensitive papers. The deposition and penetration in the lower, middle and upper parts of the plants and the runoff were also evaluated by the addition of a tracer (Brilliant Blue) to be quantified by spectrophotometry. The combination of electrostatic technology, with application rate of 200 L ha-1, and the use of adjuvant polyester polymethyl siloxane copolymer proved to be better than the other devices on the spray deposition in coffee plants, also showing the technical feasibility of using lower application rates.